2021
DOI: 10.1007/s00204-021-03174-1
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of class I HDACs and of FLT3 combine synergistically against leukemia cells with mutant FLT3

Abstract: Acute myeloid leukemia (AML) with mutations in the FMS-like tyrosine kinase (FLT3) is a clinically unresolved problem. AML cells frequently have a dysregulated expression and activity of epigenetic modulators of the histone deacetylase (HDAC) family. Therefore, we tested whether a combined inhibition of mutant FLT3 and class I HDACs is effective against AML cells. Low nanomolar doses of the FLT3 inhibitor (FLT3i) AC220 and an inhibition of class I HDACs with nanomolar concentrations of FK228 or micromolar dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…HDAC3 has key survival functions in leukemic cells of various hematopoietic lineages. These include the control of cell proliferation, apoptosis, DNA replication fork stability, and genomic integrity [31,[49][50][51][52][53][54][55]. Intriguingly, a full-body knockout of HDAC3 was not lethal in mice [56].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…HDAC3 has key survival functions in leukemic cells of various hematopoietic lineages. These include the control of cell proliferation, apoptosis, DNA replication fork stability, and genomic integrity [31,[49][50][51][52][53][54][55]. Intriguingly, a full-body knockout of HDAC3 was not lethal in mice [56].…”
Section: Discussionmentioning
confidence: 99%
“…The stronger sensitivity of such cells is consistent with the literature and multiple explanations for this have been provided for leukemic cells. These include, but are not limited to, an inhibition of the S phase-dependently induced transcription factor NF-κB [59,61,62], the induction of DNA replication stress/DNA damage [31,[49][50][51]53], inactivation of signaling through the transcription factor STAT5 [63], and a disruption of proper mitosis [64]. KH16-induced cell cycle disruptions are linked to a significant fragmentation of DNA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of HDAC6 inhibitors in cancer therapy is still a matter of debate. Recent studies showed that many cancer models are tolerant to HDAC6 inhibitor treatment (43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%